2017
DOI: 10.1002/zamm.201600064
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of electronic materials to impact loading: review

Abstract: In this review we consider publications addressing the dynamic response of electronic materials to shocks and vibrations. The emphasis is on the second level solder joint interconnections (package-to-substrate) and on the board-level drop testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Suhir and Ghaffarian [128] have recently published a review of the current work on predictive modeling of the dynamic response of electronic systems to impact loading. Suhir et al [50] suggested that not only the interfacial strength of the underfilled FC design, but also the effective elastic constants of the composite bond, can be evaluated from the shear-off data.…”
mentioning
confidence: 99%
“…Suhir and Ghaffarian [128] have recently published a review of the current work on predictive modeling of the dynamic response of electronic systems to impact loading. Suhir et al [50] suggested that not only the interfacial strength of the underfilled FC design, but also the effective elastic constants of the composite bond, can be evaluated from the shear-off data.…”
mentioning
confidence: 99%